Viewpoint: Toward a new generation of land use transport interaction models - Wee, Bert van (Journal of Transport and Land Use, 2015)
Land use transport interaction (LUTI) models are often developed to model the interaction between the land use and trans- port systems for relatively large-scale spatial developments, like new residential or office areas, new main roads, or railway lines. In this paper I argue that we need a next generation of LUTI models that model trends such as peak car; decline in population, shops, services, etc.; impact of information and communications technology (ICT) on activity patterns and travel; and cycling policies. The current genera- tion of LUTI models cannot adequately answer the policy questions raised by these trends. However, a major problem is that the future of these trends is uncertain, and we lack empirical research into the dynamics between these trends and their wider impact on land use and transport systems. Nevertheless, LUTI models can, by utilizing what-if calculations, help explore future trends and their implications. Other challenges for LUTI models include the calculation of a wider set of accessibility indicators, the inclusion of interactions between key ac- tors in the transport and land-use system—serious gaming may prove a useful way to explore these interactions—and the development of dynamic visualizations.